Kesesuaian Materi Berdasarkan Teori dan Praktek pada Bahan Ajar Bahasa Arab - Siti Aliyya Laubaha wiya; Ratni Bt H Bahri; Suleman D Kadir; muhammad Zikran Adam; Ibadurrahman Ali; Muhammad Jundi (IAI Muhammadiyah Sinjai, 2022)
This study aims to describe the content of the material based on theory and practice in Arabic textbooks in Madrasah Aliyah Class X on the material Maharah Kalam and Maharah Istima'. In this study, the author used qualitative method research with a descriptive type of approach. Researchers utilize existing sources, record, and process research materials. This library search utilizes several sources of books, journals, and articles related to the discussion material. The result of this study is that after being analyzed, the textbooks used are in accordance with theory and practice. (1) The first material, which is about the maharah Istima' based on the learning indicators of maharah Istima' is one of the processes of listening to spoken language with interest, awareness, and appreciation. 2) The second material maharah Kalam which is one of the processes to convey the message of the person who speaks to the interlocutor with a language intermediary. The suitability of the material based on theory and practice can be seen from the learning indicators in the Arabic learning book Curriculum 2013 Class X. Therefore, the two materials presented are in accordance with the theory and practice in the teaching materials.